Synthesis and physicochemical investigation of chitosan-built hydrogel with induced glucose sensitivity. Issue 16 (2nd November 2017) - Ullah, Faheem; Javed, Fatima; Othman, Muhammad Bisyrul Hafi; Ahmad, Zulkifli; Md. Akil, Hazizan
ABSTRACT: There is an urgent need to treat diabetes, and therefore, this work reports on a chitosan-built hydrogel functionalized by a glucose sensing moiety, which simulates pancreatic activity. The effect of external stimuli on various internal properties was investigated to establish the action of the hydrogel. The model drugs, fluorescein (D1) and rhodamine (D2), with a diol architecture, were investigated spectroscopically with 75.94% loading and 65.63% release. Consequently, a ligand to glucose ratio of 2:1 in comparison with a ligand to model drug ratio of 1:1 was addressed. The system was expected to lead to findings on applications for the self-controlled release of insulin in response to blood glucose levels. GRAPHICAL ABSTRACT: